PENGARUH KUALITAS AUDIT, DEBT DEFAULT, PROFITABILITAS DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN - Sinaga, Adelbertina; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of audit quality, debt default, profitability and previous year’s audit opinion on going concern audit opinion in service companies listed on the Indonesia Stock Exchange in 2015-2021. The data used is secondary data obtained from the company’s annual report. The research population includes service companies listed on the Indonesia Stock Exchange (IDX) from 2015-2021. The purposive sampling method was used in determining the sample, so that the sample consisted of 83 service companies with a total sample of 581. The data were analyzed using logistic regression performed in SPSS 25 software. The results showed that profitability has a negative effect on going concern audit opinion, previous year’s audit opinion has a positive effect on going concern audit opinion, while audit quality and debt default have no effect on going concern audit opinion.